Renosplenic Shunting in the Nutcracker Phenomenon: A Discussion and Paradigm Shift in Options? A Novel Approach to Treating Nutcracker Syndrome - Yih, Ng Deborah Chieh; Chyen, Lee Hwee; Cunli, Yang; Jaywantraj, Punamiya Sundeep; Isip, Azucena Benedict Cesar (International Journal of Angiology, 2014)
The nutcracker syndrome is a rare clinical manifestation of symptoms caused by the compression of the left renal vein by an overriding superior mesenteric artery, an anatomical variant otherwise known as the nutcracker phenomenon. Usually present in women and children, when symptomatic, it commonly presents with hematuria, proteinuria, and chronic pelvic pain. Effective modalities of treatment apart from conservative management, include both invasive surgical procedures such as renal vein transposition and autotransplantation of the kidney and more popular recently, the less invasive endovascular stenting. Both options, however, are not without complications, such as, retroperitoneal hematomas or stent migration, thrombosis and restenosis. We now present a case of spontaneous renosplenic shunting in a 68-year-old lady of Chinese descent with the nutcracker syndrome—the first of such cases to be ever reported in a patient with no preexisting predilection for chronic liver disease and portosystemic shunting. Despite having significant pelvic venous congestion as evident on computed tomography scans, she remained asymptomatic. This may present a novel paradigm shift for the treatment of the nutcracker syndrome —surgical creation of a renosplenic bypass instead of current modalities, an alternative solution which can be performed laparoscopically and is without problems related to stent use. The creation of laparoscopic splenorenal bypass has been reported once thus far in Cleveland Ohio by Chung and Gill with good symptomatic improvement but no further studies since to validate its long-term effectiveness.
Keywords: nutcracker syndrome; renosplenic shunting; splenorenal shunting; left renal vein compression; renosplenic bypass; hematuria; chronic pelvic pain; laparoscopic; minimally invasive surgery